Bribery and corruption in weak institutional environments : connecting the dots from a comparative perspective - Li, Shaomin, 1956- (Cambridge : Cambridge University Press, 2019)
Drawing on twenty years of research and observations, Li explains how bribery and corruption are carried out in countries with weak institutional environments, and how these activities become globalized. By distinguishing rule-based, relation-based and clan-based governance, this book offers a novel explanation to the age-old puzzle of why some countries thrive despite corruption. It also sheds lights on the symbiotic roles corruption and anticorruption campaigns play in maintaining dictatorships. Applying cost-benefit analysis to different governance environments, Li argues that as non-rule-based economies expand, the transition from relying on private relationships to relying on public rules is inevitable. However, by highlighting the globalization of corruption by non-rule-based countries, this book warns against the potential threats and consequences of bribery by powerful dictatorial governments. This book will appeal to scholars, analysts and graduate students studying corruption, as well as policymakers, business professionals and executives seeking insights into the characteristics of bribery and corruption within different institutional settings.
Machine generated contents note: Acknowledgements; 1. Introduction: Why Study Corruption in Countries with Weak Institutional Environments?; 2. Bribe Takers: Types of Corruption and Their Effects on Efficiency; 3. Bribe Payers: Why Do People Pay? What Do They Get? Can They Refuse To Pay?; 4. When Public Rules Meet Private Relations: The Importance of Governance Environment; 5. Why Some Societies Thrive despite Corruption: A Relation-Based Explanation; 6. Corruption And Anticorruption: Two Legs Supporting Dictatorships; 7. Paths to Transition Away from Corruption; 8. The Globalization of Corruption by Countries with Weak Institutional Environments; 9. Conclusion: Challenges And Hopes in Fighting Corruption Globally; References; Index.
Title from publisher's bibliographic system (viewed on 09 May 2019).
Keywords: Corruption; Corruption -- Prevention; Bribery; Bribery -- Prevention; Corporate governance